Anti-hypertensive effect of proteolysate generated from stone fish (Actinopyga Lecanora Jaeger) in rats - Vishkaei, Mahdokht Sadegh (2015)
Bioactive peptides within the original food-derived proteins are short sequences of amino acids that are inactive in the sequence of the parent protein. However, they can be activated through different ways including enzymatic hydrolysis. Among all the bioactive peptides, antihypertensive bioactive peptides are considered as a vitally important peptides since they are able to function as Angiotensin converting enzyme (ACE) inhibitors and have effective role in curing hypertension which is a common and serious chronic health problem and known as the most important risk factor for development of many diseases such as stroke. The ACE inhibitory effect of Actinopyga lecanora proteolysate in vitro had been reported. Hence, this study aimed to evaluate the ACE inhibitory potential of A. lecanora proteolysate in vivo (in normotensive rats). In this regard, the ACE inhibitory capability of the proteolysate to prevent increasing blood pressure, after inducing hypertension by angiotensin I was examined in normal rats. The pre-fed rats with the proteolysates at various doses (200, 400, 800 mg/kg body weight) revealed the significant (p ≤ 0.05) suppression effect compared with control groups after inducing hypertension. Furthermore, different doses of the proteolysate (200, 400, 800 mg/kg body weight) were examined to decrease the blood pressure of hypertension-induced rats. Results depicted that 800 mg proteolysate/kg body weight significantly reduced blood pressure without a negative effect on normal blood pressure (p ≤ 0.05). Sub-acute toxicity study based on OECD guideline demonstrated no toxicity effect of the proteolysate in vivo. The present study indicated that the proteolysate at a dose of 1000 mg/kg daily did not cause toxicity signs such as death, changes in activity, or piloerection. Since there are no significant differences between treated groups and control groups, hematological and biochemical analysis confirmed the safety of the proteolysate (p > 0.05). In addition, there were no significant differences between organs weights of the treated groups and the control groups. Morphologically, neither histopathological changes nor gross abnormalities were observed. However, the proteolysate caused a significant decrease in body weight in relation to the control groups (p ≤ 0.05) probably due to appetite stimulation by the proteolysate, leading to decreased food consumption in the sub-acute group. It is concluded that the proteolysate generated from A. lecanora possess a significant anti-hypertensive effect and would be potentially used as a natural alternative of ACE inhibitors.